Building a cultural heritage corridor based on geodesign theory and methodology - Yang Chen; Anrong Dang; Xia Peng (Journal of Urban Management, 2014)
Geodesign is a type of methodology that integrates dynamic environment modeling based on GIS with planning and design in order to support relevant decision making. It has substantially changed the dominant ways of thinking in planning and design, and has solved spatial issues relating to cultural and natural resources from a new perspective. Taking the Qionglai section of the Southern Silk Road as an example, the present study implemented geodesign theory and methods to investigate the technical approach to building a cultural heritage corridor based on GIS spatial analysis and overlay analysis. Firstly, we analyzed the various data layers of the cultural and natural features in the planning region. We organized all the data based on the principle of classification, organizing it into categories such as natural, cultural, and recreational data. Therefore, we defined the theme of the Southern Silk Road as a historical cultural heritage corridor. Secondly, based on the background, the heritage corridor boundary was defined according to its natural, cultural, and administrative spatial characteristics, with the three thematic boundaries overlaid in order to define a boundary location area covering about 852 square kilometers. Next, we divided all of the resources into three categories: natural heritage resources, cultural heritage resources, and intangible heritage resources and recreational spaces. The elements which could be used to build up the cultural heritage corridor were selected by evaluation and spatial analysis. In this way, we obtained some conclusive spatial information, such as element structures, the heritage density distribution, and the heritage number distribution. Finally, within the heritage boundary, we connected the tangible and intangible heritage resources to form various kinds of linear spaces, with the aim of obtaining the spatial pattern of the heritage corridor.
Keywords: 710; Geodesign; heritage boundary; heritage corridor; heritage recreation spaces; southern silk road